p21-Activated Kinase 4 Signaling Promotes Japanese Encephalitis Virus-Mediated Inflammation in Astrocytes - He, Wen (Front Cell Infect Microbiol, 2017)
Japanese encephalitis virus (JEV) targets central nervous system, resulting in neuroinflammation with typical features of neuronal death along with hyper activation of glial cells. Exploring the mechanisms responsible for the JEV-caused inflammatory response remains a pivotal area of research. In the present study, we have explored the function of p21-activated kinase 4 (PAK4) in JEV-mediated inflammatory response in human astrocytes. The results showed that JEV infection enhances the phosphorylation of PAK4 in U251 cells and mouse brain. Knockdown of PAK4 resulted in decreased expression of inflammatory cytokines that include tumor necrosis factor alpha, interleukin-6, interleukin-1β, and chemokine (C-C motif) ligand 5 and interferon β upon JEV infection, suggesting that PAK4 signaling promotes JEV-mediated inflammation. In addition, we found that knockdown of PAK4 led to the inhibition of MAPK signaling including ERK, p38 MAPK and JNK, and also resulted in the reduced nuclear translocation of NF-κB and phosphorylation of AP-1. These results demonstrate that PAK4 signaling actively promotes JEV-mediated inflammation in human astrocytes via MAPK-NF-κB/AP-1 pathway, which will provide a new insight into the molecular mechanism of the JEV-induced inflammatory response.